Effect of processing parameters on the charge storage properties of MgCo2O4 electrodes. Issue 15 (15th October 2017) - Krishnan, Syam G.; Harilal, Midhun; Misnon, Izan Izwan; Reddy, M.V.; Adams, S.; Jose, Rajan
Abstract: Three morphologies of magnesium cobaltite (MgCo2 O4 ), viz. cuboidal microcrystals, nanoflowers, and nanospheres, were synthesized using hydrothermal and molten salt methods and evaluated their electrochemical energy storage properties. Among them cuboidal microcrystal and nanoflowers were obtained by a facile hydrothermal route – the former with ethylene glycol and the latter with hexadecyltrimethylammonium bromide as surfactants. The cuboidal microcrystals showed layered flake microstructure with an appreciable space between the layers (~ 100 nm), which would facilitate ion movement between the flakes. The electrochemical studies of the materials revealed the superiority of MgCo2 O4 cuboidal microcrystals as a charge storage medium over the nanoflowers and nanospheres, the reasons for this is deeply investigated and reported herewith. The specific charge stored in the MgCo2 O4 cuboidal microcrystal electrode was ~ 345 C g −1 at a specific current of 1 A g −1 which was superior to nanoflowers (~ 178 C g −1 ) and nanospheres (~ 139 C g −1 ) at the similar current density in 3 M LiOH electrolyte. The MgCo2 O4 cuboidal microcrystals also demonstrated superior charge retention (~ 110%) after 3000 cycles over the other electrodes demonstrating its practical utility as a charge storage material.